ANALYSIS OF FACTORS AFFECTING THE INVESTMENT IN NORTH SUMATERA - ENNI SARI SIREGAR (Jurnal Education and Development, 2017)
This article focused on analyze, effect of the income, interest rates, government expenditure, and inflation to investment in North Sumatera. Data used time series of 1982 - 2012. This article use analyzer model equation with method of Two Stage Least Squared (TSLS).The result of research concludes that the income have a significant and positive impact on the investment, interest rates have significant and negatively impact on the investment, government expenditure significantly and positive on the investment, while inflation is not significant and negative effect on the investment in North Sumatera. If income increases, the investment will also increase. If interest rates increases, the investment will decreases, and If government expenditure increases, the investment will increases.